Time and society in the Qur'an: Al-Ghazali's integration of ancient wisdom into Islamic epistemology - Ruhullah, Mohammad Eisa; Ushama, Thameem (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, West Sumatra, Indonesia, 2024)
This research paper, titled explores the conceptualization of time in the Qur'an and its integration into Islamic epistemology through Al-Ghazali’s theoretical framework. The study addresses the research problem of how Qur'anic depictions of time intersect with contemporary scientific theories, particularly focusing on their implications for understanding the nature of time and its relevance to modern scientific and philosophical discussions. Utilizing a secondary descriptive analysis methodology, the research systematically reviews and compares Qur'anic verses about time with current scientific theories such as Einstein's theory of relativity and cosmological concepts. The aim is to identify points of convergence and divergence between Qur'anic insights and scientific understandings, enriching the discourse on the interplay between religious wisdom and empirical knowledge. The findings reveal a harmonious interaction between spiritual and scientific narratives, demonstrating that the Qur'an’s portrayal of time as a complex, relative phenomenon aligns with modern scientific perspectives. This integration of the Integration of Knowledge (IOK) concept fosters a holistic understanding of time, bridging theological and scientific viewpoints and contributing to broader discussions in political and democratic domains. The study underscores the significance of interdisciplinary knowledge in addressing societal issues and highlights the potential for mutual enrichment between ancient wisdom and contemporary science. Future research should continue to explore these intersections and their implications for education and societal development.